Production of homozygous lines by anther culture of heterosis of rice. I - Anther culture of heterosis lines of rice - Van, Nghiem Nhu; Bac, Le Xuan; Binh, Le Tran; Muoi, Le Thi (Academia Journal of Biology, 2015)
Production of homozygous lines by anther culture of heterosis of rice. I - Anther culture of heterosis lines of rice